Peran Manajemen Sumber Daya Manusia dalam Menciptakan Organisasi Berkelanjutan (Studi Kasus di SDN 03 Jombang) - Suroto, Suroto; Nugroho Edie Santoso; Hanif Hadinata Utama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine the implementation of human resource management (HRM) in creating a sustainable organization at SDN 03 Jombang. In the context of the ever-evolving world of education, management performance, continuous training, and transformational leadership are important factors in ensuring the sustainability of the organization. This study uses a qualitative descriptive approach with a research population consisting of the principal, five senior teachers, and three administrative staff selected by purposive sampling. Data were collected through semi-structured interviews, observations of daily activities, and document analysis related to management performance and training programs. The results of the study indicate that the implementation of HRM based on transparent performance management, relevant training, and transformational leadership contributes to improving the quality of education and operational efficiency at SDN 03 Jombang. In addition, the main challenges faced by this school are limited resources and difficulties in implementing HRM optimally. Keywords: Power, Human, Management, Organization, Resources